Development of an eco-design tool for a circular approach to building renovation projects - Bourgeois, Inês (2022)
Considering the construction sector’s impact on the environment, it is necessary amongst other measures to change the way in which new construction or renovation projects of buildings are designed and how solutions are proposed and integrated. Nowadays, an effort is being made by designers to implement more sustainable and circular design in buildings, but because of the lack of tools that can provide designers with knowledge about the impacts of the solutions to be chosen, the sustainability factor does not enter in the decision-making process as a key factor. In this sense, the development of an eco-design tool and procedure for the decision-making process will allow designers to integrate into the design phase a circular design methodology and, in a practical way, will also promote sustainability and circularity concepts as a decision factor in the construction of buildings. The present work introduces an eco-design tool that was developed to integrate circularity and sustainability information into building-renovation projects. This tool enables the evaluation and comparison of solutions based on information provided by Environmental Product Declarations (EPD) or other LCA-based calculations as well as life cycle costing information, through the generation of radar graphics that simplify the overall analysis at the decision moment. The tool was tested in a simple case study of a building renovation process and allowed designers to understand the environmental and economic impacts that each competing solution carries, either related to the materials removed from the building or to the materials coming into the buildings being renovated. In this test application, the eco-design tool proved to be able to gather quantitative information regarding environmental and economic impacts, facilitating designers to access knowledge on the different solutions impacts and help them to make a design choice based on sustainability and circularity considerations.